1962
DOI: 10.1073/pnas.48.6.1022
|View full text |Cite|
|
Sign up to set email alerts
|

Epr in Chromatophores From Rhodospirillum Rubrum and in Quantasomes From Spinach Chloroplasts

Abstract: In the penultimate paragraph of the article entitled "EPR in Chromatophores from Rhodospirillum rubrum and in Quantasomes from Spinach Chloroplasts," by G. M. Androes, M. F. Singleton, and M. Calvin, which appeared in these PRO-CEEDINGS, 48, 1022-1031(1962, the results of Chance and Nishimura were incorrectly quoted. This paragraph (on page 1030) should read as follows:"The photo-induced EPR observed in the chromatophores occurs reversibly at all temperatures studied, while that observed in the quantasomes occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1963
1963
1979
1979

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These were suspended in an aqueous medium and subjected to different conditions of illumination. Since that first experiment, this field has been studied extensively by these workers and many others (Sogo, Pon and Calvin 1957;Bubnov, Krasnovskii, Umrikhina, Tsepalov and Shliapintokh 1960;Allen, Piette and Murchio 1962;Androes, Singleton and Calvin 1962;Storey, Monita and Cadena 1962;Androes, Singleton, Biggins and Calvin 1963;Commoner, Kohl and Townsend 1963;Kohl, Townsend, Commoner, Crespi, Dougherty and Katz 1965;Kharitonenkov and Kalichava 1966).…”
Section: Photosynthetic Systemsmentioning
confidence: 99%
“…These were suspended in an aqueous medium and subjected to different conditions of illumination. Since that first experiment, this field has been studied extensively by these workers and many others (Sogo, Pon and Calvin 1957;Bubnov, Krasnovskii, Umrikhina, Tsepalov and Shliapintokh 1960;Allen, Piette and Murchio 1962;Androes, Singleton and Calvin 1962;Storey, Monita and Cadena 1962;Androes, Singleton, Biggins and Calvin 1963;Commoner, Kohl and Townsend 1963;Kohl, Townsend, Commoner, Crespi, Dougherty and Katz 1965;Kharitonenkov and Kalichava 1966).…”
Section: Photosynthetic Systemsmentioning
confidence: 99%
“…The most prominent of the photo-esr signals (Signal I) is rapidly reversible, has the free electron gvalue 2.0025, a peak-to-peak linewidth (AH) of about 7.5 g (plants) or about 9.5 g (bacteria), a Gaussian line shape, and no hyperfine structure. Subsequent esr studies (critically reviewed by Weaver (2)) on chloroplast or chromatophore preparations (3)(4)(5)(6), active-center preparations (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), organisms of unusual isotopic composition (20,21), and on in vitro chlorophyll systems (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) have made it probable that Signal I arises by the photooxidation of special chlorophyll molecules located in the photosynthetic reaction center, and that this is the chlorophyll responsible for the long-wavelength absorption associated with the reaction center (32) (P700, plants; or P870, bacteria). It has further been suggested (21) that Signal I is due to the formation of Chl+-or BChl+-; however, Signal I is much narrower than the esr signals recorded from Chl+.. To explain the unusual esr and spectral properties of reaction-center chlorophyll, chlorophyll aggregation of an unspecified nature (33), chlorophyll-lipid and chlorophyll-protein interactions (34), or perturbations in the chlorophyll -r system caused by unspecified changes in the environment (24) have been suggested.…”
mentioning
confidence: 99%
“…Low-temperature studies with R . rubrum cells and chromatophores have revealed that the ESRL signal has two components exhibiting different decay characteristics at the temperature of liquid nitrogen (Sogo et al 1959; Androes et al 1962); comparable effects can be produced at physiological temperatures by dehydrating chromatophores (Cost, Bolton & Frenkel, 1969). Under these conditions, the fast decay component of the chromatophore ESRL signal forms and decays reversibly, while the signal corresponding to the slow component is formed but does not decay.…”
Section: (E) Multiplicities In Dark Relaxation Reactions Following Phmentioning
confidence: 99%